Social Support and Fear of Cancer Recurrence Among Chinese Breast Cancer Survivors: The Mediation Role of Illness Uncertainty - Yu, Zhichao; Sun, Di; Sun, Jia (Frontiers in Psychology, 2022)
Objective To examine the relations between social support, illness uncertainty (IU), and fear of cancer recurrence (FCR). Methods Using data from a convenience sample of 231 breast cancer survivors in China to perform structural equation modeling with bootstrapping estimation. Participants were recruited from a general hospital in Shenyang, China. Participants completed the Perceived Social Support Scale, Mishel Uncertainty in Illness Scale, and Fear of Cancer Recurrence Inventory- Shorter Form. Results The majority of breast cancer survivors have FCR (67.5%). FCR was significantly negatively associated with social support, and was significantly positively associated with IU (both P < 0.01). Moreover, IU was found to mediate the relationship between social support and FCR (standardized indirect effect = –0.18; bias-corrected 95% confidence interval: –0.255, –0.123). Conclusion The findings support the final model. Good social support can directly mitigate FCR, while illness uncertainty can play a mediation role between social support and FCR. Further studies should be conducted to explore effective interventions for social support and IU to ultimately mitigate FCR in cancer survivors.